Pengaruh Servant Leadership terhadap Job Performance yang dimediasi oleh Job Attitude dan Work Behavior Karyawan pada Industri Perhotelan milik BUMN - Maria Theresia Widyastuti (International Journal of Digital Entrepreneurship and Business, 2022)
This research aims to empirically determine the effect of servant leadership on job performance mediated by job attitudes such as job satisfaction and organizational commitment as well as work behavior such as employee engagement and organizational citizenship behavior. Descriptive and explanatory surveys were adopted, and this means data were obtained through questionnaires distributed to employees at 13 SOE Hotels. Furthermore, the data were analyzed using Structural Equation Modeling (SEM) through LISREL version 8.80 data processing software. The findings showed that servant leadership has a positive and significant effect on job attitudes, work behavior, and job performance. Moreover, servant leadership mediated by job attitude and work behavior has a higher effect than its direct influence on job performance. It was also discovered that servant leadership mediated by employee engagement has the most dominant effect on job performance. This shows that job attitude represented by job satisfaction and organizational commitment as well as work behavior proxied by employee engagement and organizational citizenship behavior are effective mediators in the relationship between servant leadership and job performance. These results provide both theoretical and managerial implications that can be used to determine factors affecting employee job performance and work attitude. This model can be used as a tool to improve job performance by increasing servant leadership through the enhancement of employee engagement, job satisfaction, organization commitment, and organizational citizenship behavior.